Altered expression of epithelial-to-mesenchymal transition proteins in extraprostatic prostate cancer - Verrill, Clare; Cerundolo, Lucia; Mckee, Chad; White, Michael; Kartsonaki, Christiana; Fryer, Eve; Morris, Emma; Brewster, Simon; Ratnayaka, Indrika; Marsden, Luke; Lilja, Hans; Muschel, Ruth; et al. (Oncotarget, 2016)
Epithelial to mesenchymal transition (EMT) of cancer cells involves loss of epithelial polarity and adhesiveness, and gain of invasive and migratory mesenchymal behaviours. EMT occurs in prostate cancer (PCa) but it is unknown whether this is in specific areas of primary tumours. We examined whether any of eleven EMT-related proteins have altered expression or subcellular localisation within the extraprostatic extension component of locally advanced PCa compared with other localisations, and whether similar changes may occur in in vitro organotypic PCa cell cultures and in vivo PCa models. Expression profiles of three proteins (E-cadherin, Snail, and α-smooth muscle actin) were significantly different in extraprostatic extension PCa compared with intra-prostatic tumour, and 18/27 cases had an expression change of at least one of these three proteins. Of the three significantly altered EMT proteins in pT3 samples, one showed similar significantly altered expression patterns in in vitro organotypic culture models, and two in in vivo Pten-/- model samples. These results suggest that changes in EMT protein expression can be observed in the extraprostatic extension component of locally invasive PCa. The biology of some of these changes in protein expression may be studied in certain in vitro and in vivo PCa models.